Characterization and Formation Mechanismof Primary and Secondary School Teachers' Burdenand Ways to Relieve It - ZHANG Xueling (Jiaoshi jiaoyu xuebao)
The burdens of primary and secondary school teachers are multiple and hierarchical, characterized by a three-level gradient of superficial physical burdens, hidden psychological burdens and essential self-realization burdens. When analyzed from the perspective of the Hierarchy of Needs Theory, which divides teachers'professional needs into "material needs, " "interpersonal needs, " and "spiritual need, "the reasons for the formation mechanism of primary and secondary school teachers'burdens are as follows: at the first level, teachers'heavy workload and insufficient protection of material needs triggers teachers'subjective perception of physical burden; at the second level, the sense of belonging and respect is insufficient to make teachers unable to obtain the satisfaction of interpersonal needs, which accelerates the development of teachers'psychological burden; at the third level, the hindered teachers'self-growth and the failure to meet the expectation of spiritual needs aggravate the burden of self-fulfillment. Therefore, it is the interaction of the three reasons that aggravate the teachers'burden. That is to say, insufficient protection of "material needs" is the fuse that triggers the burden, while insufficient attention to "interpersonal needs" is the key chain that breeds the burden and low realization of "spiritual needs" catalyzes the aggravation of the burden. In order to effectively curb the growth of teacher burden in primary and secondary schools in China, multiple measures should be taken on the basis of top-level design, to clarify teachers'responsibilities to ensure their developments, specifically to improve the mechanism for safeguarding teachers'rights and interests and dynamically monitor teachers'physical burden; to build a new ecology of democratic education, respecting teachers'subjectivity and right to speak; and to reserve time for teachers'reflection and learning to provide an effective mode for teachers'growth.